PENGARUH GAYA KEMEPIMPINAN DEMOKRASI TERHADAP SEMANGAT KERJA PEGAWAI DI KECAMATAN CICURUG KABUPATEN SUKABUMI - Faradillah, Aniek; Salbiah, Euis; Hernawan, Denny (Jurnal Governansi, 2017)
The employee work enthusiasm come up from the lack of leadership adopted a leader in an organization to achieve its objectives optimally, so that leaders were able to move their subordinates. For this reason, an organization was required to have a leader who was able to create a dynamic working atmosphere and be able to improve employee work enthusiasm. Based on the research results themselves were aware that the Cicurug District employee work enthusiasm declined, it was seen from the interests of employees who work less were: in completing the job was not timely, the lack of desire was achieved, the minimum salary factor especially permanent employees, were less conducive working atmosphere, sub-district in Cicurug District who tent to use a democratic leadership style was less effective and optimal running. Based on calculation result showed that leadership style democracy in the Cicurug District in the criteria very well shown in 4.24, and for employee work enthusiasm in the Cicurug District was good criteria shown in figure 3.89. Based on the testing hypothesis results through the spearman rank correlation formula showed that the Ha accepted and Ho rejected, it meant that there was no democratic leadership style influence on employee work enthusiasm with rho calculation values of 0.24 and the coefficient of determination of 5.76%. Thus 94.24% employee work enthusiasm influenced other variables such as: 1. influence of incentives 2. Organizational work climate. Key word: Leadership style, Democration.